New Ways for Doing Extensive Reading: Hyperlearning and Cultural Context - Dewi Listia Apriliyanti; Ahmad Munir (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
Extensive reading is an effective approach to learning reading. However, this approach is sometimes criticized since it is difficult to measure the improvements in learners’ reading skills. This is due to the primary objective of extensive reading being